Influence of different drying techniques on drying parameters of mango - Izli, Nazmi; İzli, Gökçen; Taskin, Onur (Soc Brasileira Ciencia Tecnologia Alimentos, 2017)
This research inspected the effects of freeze, microwave (120 and 350 W) and hot air (60, 70 and 80 degrees C) drying techniques on the color, drying characteristics, antioxidant capacity and total phenolic content of mango slices. Midilli et al., Two-term and Page models which exemplify drying characteristics are superior than alternative models. All of the color values (a, b, L, C, a and Delta E) were altered notably based on the used drying technique and colors nearest to the fresh sample were attained with freeze drying. In comparison to the fresh sample, the dried samples showed a decrease of 18.4-54.6% in antioxidant capacity. The total phenolic content value was notably highest one for the microwave dried sample at 350 W and the lowest one for a hot air dried sample at 80 degrees C (P<0.05). This research showed that microwave drying at 350 W is able to yield high-quality mango slices with the extra advantage of shortened drying time in relation to hot air and freeze drying.
Keywords: hot air drying; freeze drying; microwave drying; modeling; quality